Microfinance – Special Case of Bolivia - Pečmanová, Anna; Chvalkovská, Jana; Urban, Traian; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
The aim of the thesis is to evaluate microfinance market in Bolivia and to make a comparison with its neighboring countries. In order to understand the microfinance sector in Latin America, brief overview of the sector is given. Moreover, the key features of Latin American model are provided in order to understand the unique development when compared to the rest of the world. Even though Bolivia has a strong microfinance sector, the decelerating tendencies have been observed over the last decade. The goal to be achieved is to prove such decelerating tendencies as well as higher growth in selected countries. The microfinance sector is analyzed according to its volume and institutional development. The research also contains the relationship between economic performance and the growth of microfinance in each country as well as the effects of political and institutional regime in Bolivia is given. The quality and character of provided services is not discussed since it would require a much deeper and comprehensive study. The researched data are based on those reported to the MIX Market, the largest portal that deals with microfinance.
Vedoucí práce: Jana Chvalkovská
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: ekonomická a regionální studia latinské ameriky [obor dipl. práce]; diplomové práce; master's theses